Comparative Gamma Delta T Cell Immunology: A Focus on Mycobacterial Disease in Cattle - Plattner, Brandon L. (SAGE-Hindawi Access to Research, 2011)
A theme among many pathogenic mycobacterial species affecting both humans and animals is a prolonged asymptomatic or latent period that can last years to decades. The mechanisms that favor progression to active disease are not well understood. Pathogen containment is often associated with an effective cell-mediated or T-helper 1 immune profile. With certain pathogenic mycobacteria, such as Mycobacterium avium subspecies paratuberculosis, a shift to active clinical disease is associated with loss of T-helper 1 immunity and development of an ineffective humoral or T-helper 2 immune response. Recently γδ T cells have been shown to play a role early in mycobacterial infections and have been hypothesized to influence disease outcome. The purpose of this paper is to compare recent advancements in our understanding of γδ T cells in humans, cattle, and mice and to discuss roles of γδ T cells in host response to mycobacterial infection.